Prevalence of thyroid disorders in antenatal patients and its feto-maternal outcome - Airao, Bhavesh B.; Patel, Nisi N.; Dholariya, Avni B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Thyroid disorders are common in pregnancy and most common disorder is subclinical hypothyroidism. Due to the complex hormonal changes during pregnancy, it is important to remember that thyroxine requirements are higher in pregnancy. Maternal hypothyroidism is an easily treatable condition that has been associated with increased risk of low birth weight, fetal distress and impaired neuropsychological development. Hyperthyroidism in pregnancy is less common as conception is a problem. Majority of them are due to Graves’ disease, though gestational hyperthyroidism is to be excluded. Early and effective treatment of thyroid disorder ensures a safe pregnancy with minimal maternal and neonatal complications. Methods: One hundred pregnant women attending antenatal clinic in first trimester were registered. Apart from routine basic and obstetrical investigations, TSH, FT3 and FT4 level estimation was done. L-thyroxine was given for hypothyroidism, this dosing was based on a study by Abalovich et al according to the body weight to maintain serum TSH near normal. For hyperthyroidism, given carbimazole if serum TSH level <1 MIU/l. Serum TSH estimation was repeated at regular interval. All the patients followed till the end of pregnancy. The normal patients served as controls. Pregnancy outcome studied statistically. Results: Around 68.8% of the inadequately treated patients developed complications like GDM, pre-eclampsia, oligohydramnios and preterm deliveries. Whereas only 32% of the control group developed these mentioned complications, this implied a significant association between inadequately treated thyroid disorders and poor pregnancy outcomes as evidenced by the p value of 0.002 which was very significant. Conclusions: Adequate treatment of thyroid disorders in pregnancy significantly reduces complications like miscarriages, pre-eclampsia, IUGR, oligohydramnios, glucose intolerance, preterm labour, low birth weight babies, abruptio placentae and stillbirth.